Color stability of steaks from carcasses vascularly infused immediately after exsanguination - Hunt, Melvin C.; Schoenbeck, J.J.; Dobbels, T.E.; Dikeman, Michael E.; Stroda, Sally L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Hereford × Angus carcasses were infused with a solution of either sugar/phosphate or calcium chloride immediately after exsanguination to determine effects on color stability during retail display. A calcium chloride solution darkened the cuts and reduced color stability. A sugar/phosphate blend made steaks appear lighter red (more desirable), and their color stability was equal to that of the noninfused control.
Keywords: Beef; Infusion; Display; Color stability